Special Commentary on Maximum Acceptable Toxicant Concentration (MATC) - Rao, K.S. (Biology, Engineering, Medicine and Science Reports)
MATC is a value that is calculated through aquatic toxicity tests to help set water quality regulations for the protection of aquatic life. Using the results of a partial life-cycle chronic toxicity test, the MATC is reported as the geometric mean between the No Observed Effect Concentration (NOEC) and the Lowest Observed Effect Concentration (LOEC).